Implementasi Metode Decision Tree Dalam Menentukan Pemberian Kredit Mobil Menggunakan Visual Basic (Studi Kasus UD PUTRA MAS Makassar) - Junaedy; Izmy Alwiah Musdar; Husni Angriani (STMIK KHARISMA Makassar, 2017)
UD Putra Mas is developing its business by granting credit on automobile purchases. The criteria of calculation used to determine the decision on credit grant is based on the amount of salary, saving, expense, credit count, and a complete set of documents. The process itself meets a couple of obstacles, such as the piling stacks of debtors’ archives in the cabinet and the difficulty in data searching. The purpose of this research is to overcome the obstacles mentioned above. The application used to develop the system is Visual Basic 6.0 and Microsoft Access 2003 as the data management media. The system created is a Decision Support System using Decision Tree Method to obtain the model. The research is based on the result of an interview with the head of UD Putra Mas to collect significant information required by the system. The output of this system is alternative of choices. This research results in a Decision Support System for Credit Grant which helps the head of UD Putra Mas in making decisions.